Gender Relations of Perpetrators and Victims of Sexual Violence During Dating Among Students - Siti Mas'udah; Salsabila Damayanti; Asbah Binti Razali; Priyono Tri Febrianto; Merlia Indah Prastiwi; Sudarso Sudarso (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Sexual violence during dating is a serious issue. The increased sexual violence during dating demonstrates that this phenomenon is becoming increasingly dangerous. This study investigates the gender relationship between perpetrators and victims of sexual violence during dating among university students. This study employed a mixed method. This study included 404 male and female students who had experienced sexual violence as respondents. This study discovered various types of sexual violence that occurred in the context of a loving relationship pattern. The perpetrators tend to control and manipulate the victim, making them want to do whatever they want. The victim loved the perpetrator excessively and was forced to serve the perpetrator’s sexual desires as a form of attention and love for the partner, even though the victim was undergoing psychological treatment. Love is transformed into a “desire to have,” causing the individual to lose himself. The subject has become an object as a result of the dating relationship. The perpetrator was repeatedly abused and was very possessive of their partner. The perpetrator did not consider their partner as a subject but rather as an object for negative emotions that significantly impacted the victim. Repeated sexual violence indicates a dating relationship that leads to a controlling relationship. This occurs because the perpetrator’s hegemony over the victim is carried out persuasively by convincing the victim to approve of the perpetrator’s actions.